Preparation and Standardization of some herbal Antidiabetic drugs in Polyherbal Formulation - Patel, Jitendra (Asian Journal of Pharmaceutics (AJP), 2025)
Background: The increasing prevalence of diabetes has heightened interest in alternative medicinal approaches, particularly those derived from herbal sources. This study focuses on synthesizing, standardizing, and evaluating a polyherbal formulation with potential antidiabetic activity. Objective: This study aims to develop and standardize a polyherbal antidiabetic formulation by integrating plant extracts with known antidiabetic properties and evaluating its therapeutic potential through in vitro studies. Methods: A combination of plant extracts was selected based on their traditional applications and pharmacological relevance in diabetes management. The bioactive compounds were extracted using suitable solvents and formulated into a standardized polyherbal product. Quality control assessments were conducted to ensure consistency and reliability, including organoleptic characteristics, extractive values, and phytochemical profiling. Standardization parameters such as total phenolic content, flavonoid content, and the presence of key bioactive components were evaluated. The glucose-lowering potential of the formulation was assessed through in vitro studies, including alpha-glucosidase inhibition assays and insulin resistance assessments. Results: Physicochemical properties, including extractive values in different solvents, moisture content, bulk and tapped density, Carr’s index, Hausner’s ratio, pH, and ash content, were analyzed to ensure formulation quality. The results indicate that these parameters are crucial in standardizing herbal antidiabetic medicines and can serve as reliable quality markers. Conclusion: This study establishes a standardized approach to developing herbal antidiabetic formulations. The findings contribute to quality control and assurance standards, providing a foundation for further clinical investigations and the development of safe and effective herbal therapies for diabetes management.